A new method to optimize protection of the organs at risk allows to regain coverage and homogeneity in the Planning Target Volume - Quintero Quintero, Alfonso; Rozo Albarracin, Edwin (Revista Brasileira de Física Médica, 2023)
The construction of auxiliary structures within the Planning Target Volume (PTV) is proposed as a method to recover coverage and homogeneity, and to optimize the protection of the organs at risk (OARs) in radiotherapy treatment plans. To this purpose, it was performed the Volumetric Modulated Arc Therapy (VMAT) treatment planning of the “mock prostate” test. Three plans were optimized in the EclipseTM treatment planning system. In plan 1 (P1), it was defined as an initial objective function only for the PTV. Then, the dose received by the OARs was restricted, guaranteeing the PTV level of coverage. Plan 2 (P2) used the same dose-volume objectives for the PTV as in P1, but more restrictive dose constraints were set for the OARs. From the dose distribution obtained in P2, it was built auxiliary sub volumes contained within the PTV to regain coverage and homogeneity in plan 3 (P3). To this end, it was compared the coverage (D95%), the Homogeneity Index (HI) and dose-volume histogram for the PTV, and OARs dose sparing for rectum and Bladder. P1 and P3 resulted in similar PTV coverage and HI values, however, the OARs received a lower dose in P3. Despite in P2 it was achieved a higher OARs protection, the PTV coverage and HI were considerably reduced. In this sense P3 allowed us to reach the best balance between coverage, HI, and OARs protection. Because of these results, it has been shown that the introduction of auxiliary structures as target sub volumes constitute a powerful and easy to implement tool in the treatment planning optimization process and can be employed in any pathology that requires VMAT.